EXPERIMENTAL EVIDENCE FOR THE CHALCOPHILE BEHAVIOR OF THE HALOGENS - Mungall J.E.; Brenan J.M. (My University, 2003)
We have investigated the partitioning of F, Cl, Br, and I between coexisting silicate and sulfide liquids at 0.9 to 1.8 GPa pressure and temperatures between 1150degrees and 1450degreesC, and the partitioning of Cl between CU- and Ni-rich sulfide liquid and monosulfide solid-solution (mss) at atmospheric pressure and temperatures of 1000degrees and 1100degreesC. We have calculated Nernst partition coefficients, expressed as wt.% halogen in sulfide divided by wt.% halogen in silicate. F remains undetectable in quenched sulfide liquid under all conditions investigated. There is no discernable change in D-Cl(sul/sil), D-Br(sul/sil) and D-I(sul/sil) with temperature. Values of D-Cl(sul/sil), D-Br(sul/sil) and D-I(sul/sil) are scattered around means of 0.038. 0.026, and 0.15, respectively. The increase of pressure from 0.9 GPa to 1.8 GPa causes increases in each of D-Cl(sul/sil), D-Br(sul/sil) and D-I(sul/sil) by about a factor of 2. Chlorine is moderately incompatible with mss; D-Cl(mss/liq) varies from 0.09 at 1000degreesC to 0.19 at 1100degreesC, indicating that crystallization of mss from sulfide liquid will lead to progressive enrichment of Cl in the residual melt. The melting point of mss in the system Fe-Cu-Ni-S is lowered by the presence of Cl. Our results indicate that the common association of halide minerals with massive sulfide ores, including the deliquescent phase lawrencite, is fully consistent with a purely magmatic origin for the ores. The halogens can be dissolved in sulfide melts, and expelled during final crystallization of the sulfide liquids to form halide minerals within the massive sulfide bodies, or hypersaline fluids when mixed with aqueous fluids in the country rocks. A hallmark of the orthomagmatic fluid derived from a sulfide magma will be extremely high values of Cl/F and Cl/Br due to the preference of Cl for sulfide relative to these other halogens. Recognition of hypersaline fluids with anomalously high Cl/Br might serve as a powerful prospecting tool in the search for Cu- and PGE-rich fractionated sulfide bodies.
Keywords: halogen; solubility; sulfide liquid; silicate liquid; monosulfide solid-solution; partition coefficient